-16=4(x-3)

Simple and best practice solution for -16=4(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16=4(x-3) equation:


Simplifying
-16 = 4(x + -3)

Reorder the terms:
-16 = 4(-3 + x)
-16 = (-3 * 4 + x * 4)
-16 = (-12 + 4x)

Solving
-16 = -12 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-16 + -4x = -12 + 4x + -4x

Combine like terms: 4x + -4x = 0
-16 + -4x = -12 + 0
-16 + -4x = -12

Add '16' to each side of the equation.
-16 + 16 + -4x = -12 + 16

Combine like terms: -16 + 16 = 0
0 + -4x = -12 + 16
-4x = -12 + 16

Combine like terms: -12 + 16 = 4
-4x = 4

Divide each side by '-4'.
x = -1

Simplifying
x = -1

See similar equations:

| (-3.4)-5/4 | | 6(4s+9)=294 | | 2y+5=6y+7 | | Y=1.5x-2.6 | | 15+6x=45x+8 | | 169+(x*x)=268.96 | | 8x+5=9x+9 | | -81=-3(-4x+5) | | 29-3m=-(m-8)+5 | | f(3)=3x^2-5x+2 | | c(c)-4c=0 | | 15(x-5)=-15 | | -2x+4x+6=26 | | p^2=-86-18p | | q=2-0 | | 6x-13-15=0 | | 2(3n-5)=(2n+5)+7 | | (u-3)*8=40 | | y=(-4)-2 | | (q-4)*4=32 | | -16t^2-17t+4=8 | | q=2-(-8) | | q-9=-7 | | (-7)+x=-15 | | 33-X=-2(1+3x) | | 18n^2+27n=0 | | -7(5b-8)+k=239 | | 5cos^2x+4cosx+1=0 | | 32=-4(k-6) | | 7-18=4y-3y+4 | | 3(5x-180+45)=-4(x-72) | | 52x(x-7)=43 |

Equations solver categories